Pharmacokinetics of cefmenoxime in patients with impaired renal function and in those undergoing hemodialysis. - Konishi, K (1986)
The pharmacokinetics of cefmenoxime were studied after a single intravenous 1.0-g dose to 24 subjects grouped according to their renal functions. Creatinine clearance was above 85, 50 to 85, 10 to 50, and below 10 ml/min per 1.73 m2 in groups 1, 2, 3, and 4, respectively. Cefmenoxime obeyed two-compartment-model kinetics in all four groups. The volume of distribution based on the area under the serum concentration-time curve was renal function independent, the average value being 0.270 +/- 0.075 liters/kg. The elimination-phase half-life (t1/2 beta) was 0.82 +/- 0.30 h in group 1, 1.38 +/- 0.36 h in group 2, 3.32 +/- 1.82 h in group 3, and 7.60 +/- 1.28 h in group 4. Cumulative 24-h urinary excretion accounted for 65.5 +/- 7.6% of the dose in group 1 and for 7.50 +/- 3.72% in group 4. Recommendations for dosage adjustment in patients with renal insufficiency are proposed based on the data obtained in this study. The effect of hemodialysis on cefmenoxime pharmacokinetics was studied in six patients in group 4; hemodialysis shortened the average t1/2 beta from 7.60 +/- 1.28 to 4.19 +/- 1.66 h. It was estimated that in a hypothetical anephric subject with a body weight of 60 kg, 5-h hemodialysis would remove 28.2% of the drug present in the body at the start of hemodialysis.